Sacral landscape and its influence on the tourism space development in the region (based on the example of Western Pomerania region NW Poland) - Duda, Tomasz (The international journal of religious tourism and pilgrimage, 2014)
Formed through the centuries, cultural landscape of the region includes not only the material realm in the form of numerous historical buildings, monuments and other evidences of local society's development, but also significant immaterial realm, which manifests itself in the form of spiritual heritage, faith, tradition, customs and language. Interesting, often unique in terms of religious and historical point of view, religious buildings, as well as traditional pilgrimage routes and local shrines are now undeniable qualities, shaping the touristic space of the region. The study of the tourism movement and a detailed valuation analysis of sacred objects showed that the wide ranging cultural tourism (with the significant participation of religious tourism) is a great alternative to still popular, although in many places it is already too saturated, leisure tourism. The historical values and a multitude of interesting, often unique objects with proper promotional activity may contribute to the tourist interest of places that often have been overlooked. The main aim of this article is to show the spatial diversity of the phenomenon of religious tourism and valuation of the landscape in terms of its usefulness as an area of cultural tourism in the region, so far perceived through the prism of seaside leisure tourism. Valuation of facilities and pilgrim routes by way of grading point while enhancing statistical information on tourism, led to create an image (a map) of the spatial diversity of the religious tourism phenomenon and its juxtaposition with other forms of tourism in the region. Thanks to this type of observations, in the future it will be possible to create a model showing the possibilities of alternative forms of tourism (including religious and cultural tourism) to formulate the touristic space. This, for example, will allow to eliminate the problems associated with the seasonality of coastal and leisure tourism, offering a new, often overlooked spaces of interest in the region.